Wind of change? Social work students' policy engagement and career preferences in Finland. - Kallio, Johanna Marketta; Jaakola, Anne-Mari; Blomberg, Helena; Kroll, Christian (Social Work Education, 2024)
Although a general mission of social workers is to advance social justice, it has been claimed that many social workers, including those studying to become social workers, have a rather weak commitment to policy engagement (PE). It has been a common assumption that Nordic social workers lack a tradition of PE due to their primary role as public employees in the comprehensive Nordic welfare state. We address these topics by empirically analyzing Finnish social work students' views toward PE. Do Finnish social work students perceive PE as an integral part of the social work profession? Moreover, if so, what ideological, sociodemographic and study-related factors explain their perceptions? Are views toward PE connected to future career preferences among students? Drawing on data from a nationwide survey among Finnish social work students, the results show that the majority of students perceive PE as important in social work. PE is explained by factors such as the respondent's political party preference, previous education and personal experiences of poverty. Students who strongly support PE are less eager to engage in individual case work with clients than other students. In addition, positive views toward PE are connected to students' preferences for working with immigrants and refugees.